Addressing land degradation benefits, costs, and policy directions - Briones, Roehlano M. (Philippine Journal of Development)
Land degradation in the Philippines is a serious environmental problem with long-term implications for the sustainability of agricultural production. Protection of the resource base has thus become a policy priority, whether in terms of improving crop management in the lowlands or more urgently, arresting soil erosion in the uplands. This review aims to compile and evaluate estimates of the costs of land degradation; then analyze the costs, benefits, and equity implications of priority measures to protect soil resources; and lastly, draw implications for policy. The review supports increasing and widening incentives for adoption of soil conservation and permanent tree crops through extension and improved tenurial measures, while ensuring that trade adjustment be accompanied by adequate social protection.